2007
DOI: 10.1523/jneurosci.3115-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Atropine- and P2X1Receptor Antagonist-Resistant, Neurogenic Contractions of the Urinary Bladder

Abstract: Acetylcholine and ATP are excitatory cotransmitters in parasympathetic nerves. We used P2X 1 receptor antagonists to further characterize the purinergic component of neurotransmission in isolated detrusor muscle of guinea pig urinary bladder. In the presence of atropine (1 M) and prazosin (100 nM), pyridoxalphosphate-6-azophenyl-2Ј,4Ј-disulfonic acid (PPADS) (0.1-100 M) and suramin (1-300 M) inhibited contractions evoked by 4 Hz nerve stimulation in a concentration-dependent manner (IC 50 of 6.9 and 13.4 M, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 42 publications
8
55
0
Order By: Relevance
“…The partial effect of PPNDS on the phasic contraction leads us to suggest that heteromeric complexes composed of the P2X1 receptor and another subtype are involved. This is in agreement with a recent study by Kennedy et al (Kennedy et al, 2007), who used pyridoxalphosphate-6-azophenyl-2', 4'-disulphonic acid (PPADS) as an alternative P2X1 antagonist.…”
Section: Rat Functional Responsessupporting
confidence: 93%
“…The partial effect of PPNDS on the phasic contraction leads us to suggest that heteromeric complexes composed of the P2X1 receptor and another subtype are involved. This is in agreement with a recent study by Kennedy et al (Kennedy et al, 2007), who used pyridoxalphosphate-6-azophenyl-2', 4'-disulphonic acid (PPADS) as an alternative P2X1 antagonist.…”
Section: Rat Functional Responsessupporting
confidence: 93%
“…α,β-meATP, an ATP analog, is a selective P2X receptor agonist and resistant to ATPase. Thus, repeated application of α,β-meATP can desensitize the P2X receptors (24,25). In the present study, the purinergic component was found to be as ~30% (field stimulation at 10 Hz) in the presence of PPADS and ~33% (field stimulation at 10 and 20 Hz) in response to desensitization with α,β-meATP both in the NC and the HC group out of ~60% atropine-resistant contractions.…”
Section: Discussionsupporting
confidence: 48%
“…We did not observe any difference in the atropine-sensitive nerve-mediated contractions between the groups in this study. P2X receptors (mainly P2X 1 ), expressed in mammalian bladders, are ATP-gated ion channels that contribute to urinary bladder functions (24,28). Several studies suggested that PPADS strongly suppresses P2X-purinoceptor-mediated contractions (25,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations